Od postulatów do społecznej praktyki. Kwestia włościańska w programie krakowskich obchodów 200-lecia odsieczy wiedeńskiej (1883) - Stachura-Lupa, Renata (Colloquia Litteraria, 2022)
The paper is dedicated to the issue of the mass participation of peasants in the 200th anniversary of the Battle of Vienna in Cracow (1883). The author pays attention to the attempts made by the organizers of the ceremony at clarifying historical knowledge about John III Sobieski and the events of 1863 to the peasant recipient, as well as analyses the role which was attributed to the peasants in the celebrations. Among the texts analysed in the article there are for example: the play by Władysław Ludwik Anczyc Kościuszko pod Racławicami and Stanisław Tarnowski’s brochure Wspomnienie o Janie III Sobieskim, królu polskim. Na pamiątkę obchodu dwóchsetnej rocznicy zwycięstwa Jana III Sobieskiego nad Turkami pod Wiedniem, which was released by the authorities of Cracow in the circulation of 25000 copies and was intended to be distributed free among the participants of this ceremony.